Family social climate and its relationship with social maturity of child 6 to 9 years - Cruz P., Mary (2013)
In this research was analyzed the relationship between cohesion, expressiveness and conflict (Family social climate) and child’s social maturity from 6 to 9 years old. We worked with the group 146 students from 1st to 4th grade of primary education, where students were between 6 and 10 years old, who were applied the family social climate scale (FSC) by Moos.E.JTrickeet, and adapted to our reality (Ruiz y Guerra, 1993) and social maturity scale proposed by Vineland (1925) adapted by Morales (Dioses 2001). The resulting proved that there is a direct relationship between the size of relations of family social climate and social maturity. There is also significant and direct components of cohesion and expressiveness to social maturity, while the component of conflict present a significant inverse relationship with the level of social maturity. So Family Social Climate directly affects social maturity in children.